Danish friends of the Soviet Union: the history of interwar Danish–Soviet organizations - Frederichsen Kim; Soimetsä Ville (Taylor & Francis, 2022)
This article presents the history of two key organizations in interwar Danish–Soviet relations, the Danish–Soviet Association (DRS) and the Danish Union of Friends of the Soviet Union (SUV). Drawing on a large selection of primary sources and literature, the article navigates considerable archival fragmentation and presents a comprehensive analysis of two parallel but separate national nodes in the wider transnational framework of Soviet cultural diplomacy. The analysis explains the background, structures, activities, and relevance of the Comintern-organized SUV and the non-party-affiliated DRS and demonstrates how both associations were relatively successful in both the Danish and Scandinavian contexts throughout the interwar period. The organizations’ resilience was bolstered by the comparatively good cohesion of the Danish Communist Party, and widely respected people in key positions.